(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article is devoted to the definition and analysis of features lexical units representing human mental activity, and also isomorphic, allomorphic and linguocultural features phraseological units with the head/bosh component in English and Uzbek languages.